EVALUATION OF INNOVATED FORMULA OF BISACODYL SUPPOSITORY FOLLOWING THE DISSOLUTION PROFILE AND STABILITY DATA USING DEVELOPED HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD - J HASSON, KAHTAN; G JABAR, ESRAA; I ALKHALIFA, IHAB (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Bisacodyl is a laxative drug used in the treatment of constipation, it is soluble in mineral acids, but it is practically insoluble in water. Therefore, it is very hard task to dissolve bisacodyl in alkaline medium so the objective of this study was the development of proper dissolution method for a new formulation of bisacodyl suppositories in a medium simulated to rectal region. Obviously, most of the bisacodyl suppositories preparation products will yield low percentages of dissolution in the alkaline medium of phosphate buffer pH 7.2. Methods: Preparation inclusion complex of bisacodyl with the solubilizing agent beta-cyclodextrin then incorporated in a suppository base. The quantitative analysis of bisacodyl in suppositories was carried by a developed and validated high-performance liquid chromatography method. Results and Discussion: The dissolution rates for the innovated formulation of bisacodyl complexed with beta-cyclodextrin suppositories were in average of 97.5% and the stored suppositories of this formulation maintained their specified physical and chemical properties along the real stability study. Conclusion: The application of the inclusion complexation technique of bisacodyl with beta-cyclodextrin in the production of suppositories enhances the dissolution rate and improves the stability of suppositories performance.